Long-term yield and weed response to conservation and stubble tillage in SW Germany - Gruber, Sabine; Pekrun, Carola; Möhring, Jens; Claupein, Wilhelm (Soil & tillage research, 2012)
► We evaluate seven different modes of tillage in long-term experiments in Germany. ► Only no-tillage results in yield loss amongst all treatments. ► No effect of stubble tillage and of inversion vs. non-inversion tillage on yield. ► Few effects of stubble and inversion vs. non-inversion tillage on weed. ► Low extrinsic restrictions on choice of mode of tillage in a temperate climate. The study provides information to more reliably estimate the value of conservation tillage in a temperate climate. Tillage effects on yield and weeds were evaluated in field experiments at two sites in SW Germany between 1999 and 2010. Tillage varied at site Ihinger Hof from mouldboard plough (P), chisel plough (CP), rototiller (RTT), varying P and CP (VAR), to no tillage (NT), partially combined with stubble tillage (S). Tillage at site Meiereihof was S/P, S/CP, and NT. Crop rotations included winter wheat (WW, Triticum aestivum), triticale (TR, Triticosecale), oat (OA, Avena sativa), silage maize (SM, Zea mays) and oilseed rape (OSR, Brassica napus) at Ihinger Hof, and winter wheat, spring barley (SB, Hordeum vulgare), silage maize, sugar beets (SBE, Beta vulgaris) and faba bean (FB, Vicia faba) at Meiereihof. At Ihinger Hof, tillage had an effect on yield (P>F=0.0049), but no effects were found on crop emergence and crop density. Tillage effects on yield were consistent across crops though differences between crops appeared to exist. The yield of S/P, the standard tillage, was 8.5 (WW), 7.7 (TR), 4.7 (OA), 18.3 (SM) and 4.1 (OSR)tDMha−1 at Ihinger Hof, with yield under NT always significantly lower than S/P by 7.3% on average for all crops. At Meiereihof, yields ranged from 7.2 to 8.0 (WW), 3.3 to 4.2 (SB), 19.8 to 21.5 (SM) and 3.1 to 3.2 (FB)tDMha−1, and 61.3 to 67.6 FM ha−1 for SBE. Yield was reduced by 4.5% from S/P to S/CP (P>F=0.0516), and by about 10% from S/P to NT (P>F=0.0009). Weed density ranged between 0.5 and 44plantsm−2 at Ihinger Hof and was higher in treatments without stubble tillage and under non-inversion tillage, though significance differed for the different classes of weeds. NT led to weed infestation about 2–20 times higher than S/P. The interaction crop×treatment indicated that factors other than tillage influenced weed infestation. It is unlikely that weed infestation and reduced yield will be problems in temperate climates if soil disturbance through tillage is reduced. Non-inversion tillage can easily replace inversion tillage, and stubble tillage can be added to primary tillage if needed to reduce weeds. Since no specific tillage method was unequivocally superior to another one, any method well suited to specific regional and farm conditions can be adopted successfully.